Share Market Response to the Announcement of Dividend Payment Plan in the Food and Beverage Sector Registered in Indonesia Stock Exchange - Faizal Aga Hamanda; Mursidi Mursidi; Warsono Warsono (Universitas Muhammadiyah Malang, 2021)
The purpose of this study is to determine investors' reactions to the announcement of the 2017-2019 dividend payment plan in the food and beverage sector listed on the Indonesia Stock Exchange. This type of survey is an empirical survey using the event survey method which aims to investigate the market reaction to events whose information is published as announcements. The data used in this study is secondary data, namely data taken from other data sources, not collected by the researcher himself. Data obtained from the Indonesia Stock Exchange Corner. The data analysis method is to calculate the actual daily stock return for each stock during the event and use the expected model to estimate the expected return. When we tested the comparison of the average rate of return (AAR) of stocks during the pre-announcement period, the average rate of return was -0.065813, but seven days after the announcement, the average rate of return was -0.000720. We tested the difference between 15 days before the announcement and 15 days after the announcement and found that the t-value was 2.996 and the significance was 0.001.